2023
DOI: 10.3389/fendo.2023.1261781
|View full text |Cite
|
Sign up to set email alerts
|

Estrobolome dysregulation is associated with altered immunometabolism in a mouse model of endometriosis

Hasan Alghetaa,
Amira Mohammed,
Narendra P. Singh
et al.

Abstract: IntroductionEndometriosis is a painful disease that affects around 5% of women of reproductive age. In endometriosis, ectopic endometrial cells or seeded endometrial debris grow in abnormal locations including the peritoneal cavity. Common manifestations of endometriosis include dyspareunia, dysmenorrhea, chronic pelvic pain and often infertility and symptomatic relief or surgical removal are mainstays of treatment. Endometriosis both promotes and responds to estrogen imbalance, leading to intestinal bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In addition, recent studies have found a complex relationship between SCFAs and EMS. Metabolomics showed reduced short-chain fatty acids in a mouse model of endometriosis (Alghetaa et al, 2023). Studies by Chadchan et al also found that short-chain fatty acids were reduced in the feces of mice with endometriosis, and treatment with nbutyrate reduced the growth of endometriosis lesions in mice (Chadchan et al, 2021).…”
Section: Endometriosismentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, recent studies have found a complex relationship between SCFAs and EMS. Metabolomics showed reduced short-chain fatty acids in a mouse model of endometriosis (Alghetaa et al, 2023). Studies by Chadchan et al also found that short-chain fatty acids were reduced in the feces of mice with endometriosis, and treatment with nbutyrate reduced the growth of endometriosis lesions in mice (Chadchan et al, 2021).…”
Section: Endometriosismentioning
confidence: 96%
“…In addition, recent studies have found a complex relationship between SCFAs and EMS. Metabolomics showed reduced short-chain fatty acids in a mouse model of endometriosis ( Alghetaa et al., 2023 ). Studies by Chadchan et al.…”
Section: Gut Microbiota Metabolites: Scfasmentioning
confidence: 99%
“…Moreover, the physiological significance of gus -enriched bacteria such as Ruminococcus spp. merits attention, given their direct impact on steroid metabolism in the intestinal milieu, thus potentially modulating the pathophysiology of estrogen-related dysfunctions [ 14 ]. More explorations involving more tissue types and bioinformation are needed to reveal these complex mechanisms.…”
Section: Introductionmentioning
confidence: 99%